2011
DOI: 10.1371/journal.pone.0023230
|View full text |Cite
|
Sign up to set email alerts
|

TIG3 Tumor Suppressor-Dependent Organelle Redistribution and Apoptosis in Skin Cancer Cells

Abstract: TIG3 is a tumor suppressor protein that limits keratinocyte survival during normal differentiation. It is also important in cancer, as TIG3 level is reduced in tumors and in skin cancer cell lines, suggesting that loss of expression may be required for cancer cell survival. An important goal is identifying how TIG3 limits cell survival. In the present study we show that TIG3 expression in epidermal squamous cell carcinoma SCC-13 cells reduces cell proliferation and promotes morphological and biochemical apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…We previously reported that TIG3 reduces cell survival (Jans et al, 2008;Scharadin et al, 2011;Sturniolo et al, 2003); however, little is known about the mechanism of growth suppression. In the present study, we demonstrate that TIG3 localizes to the centrosome, as shown by colocalization with the centriole and centrosome markers, c-tubulin and pericentrin.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that TIG3 reduces cell survival (Jans et al, 2008;Scharadin et al, 2011;Sturniolo et al, 2003); however, little is known about the mechanism of growth suppression. In the present study, we demonstrate that TIG3 localizes to the centrosome, as shown by colocalization with the centriole and centrosome markers, c-tubulin and pericentrin.…”
Section: Discussionmentioning
confidence: 99%
“…TIG3 localizes to the plasma membrane and at the centrosome in normal keratinocytes and skin cancer cells (Sturniolo et al , 2005; Sturniolo et al , 2003; Scharadin et al , 2011; Scharadin et al , 2012). The C-terminal hydrophobic region serves to anchor TIG3 to the cell membrane (Deucher et al , 2000; Sturniolo et al , 2005; Sturniolo et al , 2003) where it activates transglutaminase.…”
Section: Introductionmentioning
confidence: 99%
“…Both genes are expressed in normal tissues in a tissue-specific manner and are downregulated in various cancer tissues [15-18]. These proteins exhibit growth-suppressive activities when ectopically expressed in various types of cancer cells and RAS-transformed fibroblasts [6,8,11,13,19-22]. In addition, terminal differentiation of keratinocytes has been observed in cells with induced RIG1 expression [13,23].…”
Section: Introductionmentioning
confidence: 99%